Public trust to institutions as a resource of interethnic consolidation in the regional community - V. V. Krivopuskov (Цифровая социология)
The article is devoted to the phenomenon of trust in terms of the resource to achieve interethnic consolidation in the Russian regional community. The article indicates that trust allows developing a communication mechanism and defining how effectively social relations are built. Besides, the author uses traditional sociological research methods: structuralist and institutional approaches, social capital theory. Trust is one of the socio-psychological foundations of social harmony that determines the dynamics of basic social processes development, the integrity of society, its ability to overcome the arising difficulties. With the help of the array of secondary data analysis presented on the websites of domestic sociological centres, it is shown how in the Russian society the importance of national consolidation is clearly increasing. It is based on the increased trust at all levels of relationships: interpersonal, intergroup, institutional, and regional. This is due to the fact that Russia is one of the most multinational states in the world. If citizens do not share certain common goals and objectives, then this, as a rule, will negatively affect the interethnic consolidation of the regional or entire community of the country most. Undoubtedly, the phenomenon of trust is especially important in the transforming society. It exists in the multiethical environment of citizens and, first of all, directly at the regional level of the institutions, functioning in Russia. Trust is an indicator of values similarity and values systems of the Russian population. Today there are many examples of the decrease of trust to certain institutions, however, the approval rating regarding the activities of the President, the Government of the country, the Russian army is increasing. Thus, a positive attitude of Russians towards the political system and power structures is recorded. The same trends have begun to be noted more often in the field of interethnic consolidation and in relation to the institutions of the regional community.